A Biofunctional Molecular Beacon for Detecting Single Base Mutations in Cancer Cells - Haiyan Dong; Ji Ma; Jie Wang; Zai-Sheng Wu; Patrick J Sinko; Lee Jia (Elsevier, 2016)
The development of a convenient and sensitive biosensing system to detect specific DNA sequences is an important issue in the field of genetic disease therapy. As a classic DNA detection technique, molecular beacon (MB) is often used in the biosensing system. However, it has intrinsic drawbacks, including high assay cost, complicated chemical modification, and operational complexity. In this study, we developed a simple and cost-effective label-free multifunctional MB (LMMB) by integrating elements of polymerization primer, template, target recognition, and G-quadruplex into one entity to detect target DNA. The core technique was accomplished by introducing a G-hairpin that features fragments of both G-quadruplex and target DNA recognition in the G-hairpin stem. Hybridization between LMMB and target DNA triggered conformational change between the G-hairpin and the common C-hairpin, resulting in significant SYBR-green signal amplification. The hybridization continues to the isothermal circular strand-displacement polymerization and accumulation of the double-stranded fragments, causing the uninterrupted extension of the LMMB without a need of chemical modification and other assistant DNA sequences. The novel and programmable LMMB could detect target DNA with sensitivity at 250 pmol/l with a linear range from 2 to 100 nmol/l and the relative standard deviation of 7.98%. The LMMB could sense a single base mutation from the normal DNA, and polymerase chain reaction (PCR) amplicons of the mutant-type cell line from the wild-type one. The total time required for preparation and assaying was only 25 minutes. Apparently, the LMMB shows great potential for detecting DNA and its mutations in biosamples, and therefore it opens up a new prospect for genetic disease therapy.